The rise of silver-haired influencers: Intergenerational emotional compensation and the emotional needs of Chinese Youth on Douyin - LIANG, Wenrui; Shamshudeen, Rosya Izyanie; Syed, Md Azalanshah Md (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates how silver-haired influencers on Douyin serve as digital mediators for intergenerational emotional compensation among Chinese youth. The research seeks to understand the mechanisms by which these influencers evoke feelings of nostalgia for elders and address the emotional needs of young users separated from their families due to geographic mobility. The study adopts a qualitative methodology, employing semi-structured interviews with 23 Chinese youth aged 18–24 who have followed silver-haired influencers on Douyin for more than six months. Interview data were analyzed thematically, focusing on emotional responses, psychological motivations, and the perceived role of digital interaction in mediating intergenerational bonds. The results reveal that silver-haired influencers evoke youth nostalgia for elders in three primary ways: nostalgic storytelling, simulated digital intimacy, and algorithmic amplification. The study identifies three key compensatory effects for youth: alleviation of guilt over not accompanying elders, regret for family separation, and reinforcement of self-esteem. These influencers function as symbolic surrogates, offering both emotional comfort and cultural connection in the context of familial estrangement. Silver-haired influencers on Douyin play a significant role in fulfilling the emotional and psychological needs of Chinese youth who are geographically distant from their families. While digital interactions provide meaningful emotional relief and foster a sense of virtual familial belonging, they cannot fully substitute for real-life intergenerational relationships. The findings extend the application of psychological and emotional compensation theory to the context of social media, highlighting the unique contributions of digital platforms in shaping intergenerational connections. This research offers actionable insights for platform designers, policymakers, and practitioners seeking to strengthen intergenerational ties in digital society. The dual compensation framework proposed in this study suggests new directions for digital content strategies and aging policy, emphasizing the social value of elderly influencers as emotional mediators in contemporary China.